Study on Consumers Attitude Preferences and Satisfaction Level towards Selected Branded Paints - Kumar Chaudhary, Kuldeep; Madhukar, Vikas (International Journal of Psychosocial Rehabilitation, 2020)
India is the second biggest paint showcase in Asia with a yearly interest of more than two million tons. The Indian paint industry has been becoming continually in the course of the most recent decade. Development has been reliable with the GDP development rate and in a few years significantly higher. In the course of recent years, the Indian paint showcase has considerably developed and grabbed the eye of numerous worldwide players. The nation keeps on getting a charge out of a solid development rate contrasted with different economies, sponsored by the expanding dimension of discretionary cashflow, and request from framework, mechanical and car parts. This Paper centers around Understanding client mindfulness towards Paint and Factors Influencing his basic leadership.